Natural history of functional mitral regurgitation: a systematic review and individual patient data meta-analysis. (25th January 2023) - Teo, Y N; Basker, G; Teoh, S E; Tan, E W X; Teo, Y H; Chai, P; Wong, R C C; Yip, J W L; Kuntjoro, I; Lim, Y; Poh, K K; Yeo, T C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Ching-Hui Sia was supported by the National University of Singapore Yong Loo Lin School of Medicine's Junior Academic Fellowship Scheme. Background: Functional mitral regurgitation (FMR) precipitates a vicious cycle of left ventricular volume overload and remodelling, leading to perpetual worsening of FMR and left ventricular dysfunction, with a resultant poor prognosis. However, there is a lack of conclusive data on the natural progression of FMR in patients who do not undergo valvular intervention. Purpose: We performed a one-stage meta-analysis on reconstructed individual patient data (IPD) to elucidate the natural history of FMR. Methods: Four databases (PubMed, Embase, Scopus, Cochrane) were searched for randomised controlled trials or cohorts, published from inception to March 13, 2022, reporting clinical outcomes in patients with FMR not receiving valvular intervention. IPD meta-analysis, as the gold standard approach for evidence synthesis, was performed with reconstructed IPD obtained from the survival curves reported in the included studies. Pooled survival estimates were derived. Quality assessment of included studies was conducted using the Cochrane risk-of-bias tool and Newcastle Ottawa Scale. This study was registered on the International Prospective Register of Systematic Reviews. Results: A total of five studies were included, comprising a total cohort of 691 patients with FMR who did not undergo valvular intervention. The mean age of the cohort was 72.4 years (95% CI 67.6 to 77.1) and the proportion of males was 61.1% (95% CI 43.8 to 76.0). All-cause mortality was analysed over a follow-up duration of five years, while hospitalisation for heart failure, cardiovascular death, and the composite of all-cause mortality and hospitalisation for heart failure were analysed over a follow-up duration of three years. The probability of survival of patients with FMR without intervention was 79.4% (95% CI 76.2 to 82.3), 50.9% (95% CI 46.6 to 55.1), and 39.6% (95% CI 33.1 to 46.0) at one, three, and five years respectively. The probability of survival free from the composite of all-cause mortality and hospitalisation for heart failure was 51.3% (95% CI 46.8 to 55.6) and 12.0% (95% CI 8.9 to 15.7) at one year and three years respectively. The probability of survival free from hospitalisation for heart failure was 58.3% (95% CI 54.0 to 62.3) and 19.7% (95% CI 16.0 to 23.7) at one and three years respectively. The probability of survival free from cardiovascular death was 75.4% (95% CI 68.9 to 80.8) and 45.6% (95% CI 29.1 to 60.7) at one and three years respectively. All included studies were of low to moderate risk of bias. Conclusion: FMR in the absence of valvular intervention is associated with poor survival and cardiovascular outcomes. Further research should focus on the role of interventions to mitigate its poor prognosis.